Information Security in The Cloud Era: Strategies and Implementation - Nyoman Gunantara (Pt. Anagata Sembagi Education, 2025)
Cloud computing has become a fundamental driver of global digital transformation, providing organizations with scalability, operational efficiency, and flexibility. However, the migration to cloud environments has also intensified cybersecurity challenges, including data breaches, misconfigurations, identity compromise, and evolving cyber-threats. This systematic literature review analyzes strategic and implementation approaches to cloud information security across multiple sectors. The study applies a structured methodology aligned with academic SLR standards to identify key security practices, technological controls, and governance frameworks. Findings reveal that effective cloud security requires a holistic model integrating Zero Trust Architecture, encryption, identity and access management, artificial intelligence-driven threat monitoring, and compliance with regulatory frameworks. Organizational readiness, human capability, and governance maturity significantly influence implementation outcomes. The study concludes that adaptive, multi-layer security models combined with continuous workforce development and regulatory harmonization are critical for building sustainable cloud resilience